Flatly broadened supercontinuum generation in nonlinear fibers using a mode locked bismuth oxide based erbium doped fiber laser - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Akbari, Reza; Ahmad, Harith (IOP Publishing, 2011)
Supercontinuum generation with considerable flatness and low fluctuation is investigated in nonlinear fibers by amplification of pulsed seed signal of a stable mode locked bismuth oxide based erbium doped fiber laser. Spectral expansion from 980 to 1750 nm is obtained by 340 fs pulses at 1560 nm amplified up to 177 kW in a dispersion flattened highly non-linear fiber. A comparison is made for different types of nonlinear fibers and evaluation of spectral bandwidth at high powers is probed.